Concentration of Gallbladder Phosphatidylcholine in Cholangiopathies: A Phosphorus‐31 Magnetic Resonance Spectroscopy Pilot Study - Pfleger, Lorenz; Halilbasic, Emina; Gajdošík, Martin; Benčíková, Diana; Chmelík, Marek; Scherer, Thomas; Trattnig, Siegfried; Krebs, Michael; Trauner, Michael; Krššák, Martin (Journal of magnetic resonance imaging, 2022)
Background Biliary phosphatidylcholine (PtdC) concentration plays a role in the pathogenesis of bile duct diseases. In vivo phosphorus‐31 magnetic resonance spectroscopy (31P‐MRS) at 7 T offers the possibility to assess this concentration noninvasively with high spectral resolution and signal intensity. Purpose Comparison of PtdC levels of cholangiopathic patient groups to a control group using a measured T1 relaxation time of PtdC in healthy subjects. Study Type Case control. Subjects Two patient groups with primary sclerosing cholangitis (PSC, 2f/3 m; age: 43 ± 7 years) and primary biliary cholangitis (PBC, 4f/2 m; age: 57 ± 6 years), and a healthy control group (CON, 2f/3 m; age: 38 ± 7 years). Ten healthy subjects for the assessment of the T1 relaxation time of PtdC. Field Strength/Sequence A 3D phase‐encoded pulse‐acquire 31P‐MRSI sequence for PtdC quantification and a 1D image‐selected in vivo 31P spectroscopy for T1 estimation at 7 T, and a T2‐weighted half‐Fourier single‐shot turbo spin echo MRI sequence for volumetry at 3 T. Assessment Calculation of gallbladder volumes and PtdC concentration in groups using hepatic gamma‐adenosine triphosphate signal as an internal reference and correction for insufficient relaxation of PtdC with a T1 value assessed in healthy subjects. Statistical Tests Group comparison of PtdC content and gallbladder volumes of the PSC/PBC and CON group using Student's t‐tests with a significance level of 5%. Results PtdC T1 value of 357 ± 85 msec in the gallbladder. Significant lower PtdC content for the PSC group, and for the female subgroup of the PBC group compared to the CON group (PSC/CON: 5.74 ± 0.73 mM vs. 9.64 ± 0.97 mM, PBC(f)/CON: 5.77 ± 1.44 mM vs. 9.64 ± 0.97 mM). Significant higher gallbladder volumes of the patient groups compared to the CON group (PSC/CON: 66.3 ± 15.8 mL vs. 20.9 ± 2.2 mL, PBC/CON: 49.8 ± 18.2 mL vs. 20.9 ± 2.2 mL). Data Conclusion This study demonstrated the application of a 31P‐MRSI protocol for the quantification of PtdC in the human gallbladder at 7 T. Observed differences in PtdC concentration suggest that this metabolite could serve as a biomarker for specific hepatobiliary disorders. Level of Evidence 2 Technical Efficacy Stage 3